Machinability of rectangular bars of nodular cast iron produced by continuous casting - de Sousa J.A.G. (2018)
© 2018, Springer-Verlag London Ltd., part of Springer Nature.Continuous bars of ductile iron are widely used for parts produced by machining processes, for example, hydraulic manifolds, hydraulic cylinder pistons, bushings, and pump housings. The main reasons for the selection of ductile iron bars are the high strength, stiffness, toughness, wear resistance, cost, and machinability. Concerning this last property, the best machinability is obtained for a ductile iron with a predominantly soft ferritic matrix. The rate of the solid-state transformation of austenite into ferrite, the so called “stable eutectoid reaction,” is dependent on the diffusion distance from the austenite to graphite particles, in other words, on the maximum distance between the graphite particles. If this distance increases, the time for the reaction may not be sufficient, and a “metastable eutectoid reaction” can occur, with the decomposition of austenite into pearlite, a mixture of soft ferrite with iron carbide. This constituent, called pearlite, shows higher hardness than ferrite, and so it must be machined under different conditions compared with a ferrite matrix. Thus, the distance between the graphite particles, measured by the number of graphite particles per unit area, determines the type of ductile iron matrix. The number of graphite particles is governed mainly by the solidification speed. In the continuous casting of bars of ductile iron, there is a variation in the solidification speed from the surface of the bar to the center of the section, decreasing toward the center. This is particularly important in thick sections, where the difference in the solidification speed is significant, leading to a variation in the microstructure from the surface to the center. This variation in the microstructure was the focus of this study, measuring various parameters connected to machinability, such as torque, power consumption, tool life (with tool wear analysis), and surface roughness. The goal was to show that the machining conditions must be changed when machining different positions on the section of a thick continuous ductile iron bar. Lower torque and shorter tool life were obtained when cutting the core in relation to the periphery region. However, in terms of power consumption and surface roughness, there was no statistical difference between the regions evaluated during the milling process. The variability of the machining output parameters is related to the mechanical properties along the cross section of the bars.